VERSTEK DECISION IN DIVORCE CASE IN RELIGIOUS COURTS OF RANTAUPRAPAT - Risdalina Risdalina; Kusno Kusno; Bernat Panjaitan; Maya Jannah (International Journal Labs, 2022)
Background: In a Civil Judgment, one of which is called a Verstek Judgment, there is a divorce case trial process, the Panel of Judges has the authority to decide cases in accordance with applicable laws and regulations. Verstek is a judgment rendered by a judge in the absence of the Defendant at trial even though the Defendant has been duly summoned by the bailiff of the court. Therefore the judge can decide the case with a verstex verdict. The author took the research site at the Rantauprapat Religious Court. Objective: The purpose of this study was to analyze verstek decisions in divorce cases in rantauprapat religious courts. Methods: The method used in this writing is the Empirical normative method, which is research based on the provisions of applicable laws and regulations by looking at the implementation conditions in the field. Results: The Rantauprapat Religious Court is domiciled in Labuhanbatu Induk Regency which is in charge of North Labuhanbatu Regency and South Labuhanbatu Regency, which has the duty and authority to receive, examine, adjudicate, decide and settle cases of marriage, inheritance, wills, grants, waqf, and alms as well as resolve disputes in the field of sharia economy among Muslims to uphold law and justice, as stipulated in Law Number 3 Year 2006 concerning amendments to Law Number 7 of 1989 concerning Religious Courts. Conslusion: Verstek Decision Legal Remedies in Divorce Cases is by filing a challenge against the verstek decision within 14 (fourteen) days after the notification is received by the defendant.